Iroquois - Bird, F. A. (Bird, F. A. Native American nations., 2022)
"This book introduces young readers to the Iroquois people, their traditional ways of life, including social structure, homes, food, art, clothing and more, their contact with Europeans, and how the Iroquois are keeping their culture alive today"--Publisher.